2014
DOI: 10.1002/ejoc.201402083
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Blennolide Mycotoxins: Design, Synthetic Routes and Completion

Abstract: Mycotoxins of the tetrahydroxanthone class of natural products possess a large number of interesting biological properties. In this full paper, we present our synthetic strategy to some members of this class of compounds, namely the blennolides A and C. We disclose the scope and limitations of the functionalization of various xanthones derived from a domino oxa‐Michael‐aldol condensation and pursue dimerization of these xanthones. Furthermore, the first crystal structure of blennolide C has been obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…1,2 In particular, biaryl dimeric tetrahydroxanthones have gained signicant interest recently, not only because of their intriguing antibacterial and anticancer activities, but also owing to the synthetic challenges posed by their structures. Recent work from the groups of Bräse, [3][4][5][6][7]21,22 Nicolaou, 8 Tietze, [9][10][11]18,19 Porco, 12,[15][16][17] Kumamoto, 13 and Gao 14,20 et al has shown signicant progress in the synthesis of tetrahydroxanthone monomers [3][4][5][6][7][8][9][10][11][12][13][14] or homodimeric tetrahydroxanthones. [15][16][17][18][19][20][21][22] To the best of our knowledge, heterodimeric biaryl tetrahydroxanthones have rarely been synthesized, largely due to the synthetic challenges in assembling their sterically hindered biaryls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 In particular, biaryl dimeric tetrahydroxanthones have gained signicant interest recently, not only because of their intriguing antibacterial and anticancer activities, but also owing to the synthetic challenges posed by their structures. Recent work from the groups of Bräse, [3][4][5][6][7]21,22 Nicolaou, 8 Tietze, [9][10][11]18,19 Porco, 12,[15][16][17] Kumamoto, 13 and Gao 14,20 et al has shown signicant progress in the synthesis of tetrahydroxanthone monomers [3][4][5][6][7][8][9][10][11][12][13][14] or homodimeric tetrahydroxanthones. [15][16][17][18][19][20][21][22] To the best of our knowledge, heterodimeric biaryl tetrahydroxanthones have rarely been synthesized, largely due to the synthetic challenges in assembling their sterically hindered biaryls.…”
Section: Introductionmentioning
confidence: 99%
“…35 And benzoxaborole 16 could be derived from tetrahydroxanthone monomer 17. Although several effective strategies are developed by Bräse, [3][4][5][6][7] Nicolaou, 8 Tietze, [9][10][11] Porco, 12 Kumamoto 13 and Gao 14 groups in the preparation of the chiral tetrahydroxanthone structure, a highly enantioselective and diastereoselective version would be highly desirable. We anticipated that 17 could be efficiently synthesized from 18 and a known chiral intermediate 19 (ref.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] As shown in Figure 1, α-tocopherol is one of the most prominent chiral chromans in the vitamin E family, which acts as an efficient radical-chain-breaking antioxidant in tissues. [3,4] Moreover, tocopherols and their derivatives also exhibit anti-inflammatory, antitumor, anti-atherosclerosis, and cell-signaling physiological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Natural products and secondary metabolites of microorganisms containing a chiral chroman or chroman‐derivative (e.g., chromene, chromanone, tetrahydroxanthone) skeleton possess a large number of interesting biological properties (Figure 1). 1,2 As shown in Figure 1, α‐tocopherol is one of the most prominent chiral chromans in the vitamin E family, which acts as an efficient radical‐chain‐breaking antioxidant in tissues 3,4. Moreover, tocopherols and their derivatives also exhibit anti‐inflammatory, antitumor, anti‐atherosclerosis, and cell‐signaling physiological activities 57.…”
Section: Introductionmentioning
confidence: 99%
“…Related hybrid chromone lactone/tetrahydroxanthones including the 2,4'-linked heterodimer gonytolide E ( 3 ) 14 and the 4,4'-linked chromone lactone homodimer gonytolide A ( 4 ) 15 have also been reported. Recently, these interesting molecules have attracted significant interest in the synthetic community as evidenced by reports of syntheses of both monomeric 16 , 17 , 18 , 19 , 20 , 21 , 22 and dimeric natural products. 23 However, syntheses of tetrahydroxanthones bearing axial chirality including rugulotrosin A ( 1 ) and related compounds have not been reported.…”
mentioning
confidence: 99%